Isolation of microfibrillated cellulose (MFC) via fungal cellulases hydrolysis combined with ultrasonication - Jimat, Dzun Noraini; Avicenna, Avicenna (Springer Nature, 2018)
Celluloses, the most abundant biopolymers which exist in plant sources have become potential materials in many applications due to theirs fascinating structure and properties. In plant cell walls, they are embedded in matrix substances such as hemicellulose and lignin. Removal of matrix substances is required before fibrillating the cellulose fibres into nanoscale-sized. The obtained microfibrillated cellulose (MFC) poses different features depending to its origin and degree of processing procedures and fibrillation method use. Thus, this chapter explains the isolation steps of microfibril cellulose (MFC) from cocoa pod husk via fungal cellulases hydrolysis combined with ultrasonication.